Remote ischaemic postconditioning protects the heart during acute myocardial infarction in pigs. Issue 6 (20th April 2007) - Andreka, Gyorgy; Vertesaljai, Marton; Szantho, Gergely; Font, Gusztav; Piroth, Zsolt; Fontos, Geza; Juhasz, Eszter D; Szekely, Laszlo; Szelid, Zsolt; Turner, Mark S; Ashrafian, Houman; Frenneaux, Michael P; et al.
Abstract : Background: Ischaemic preconditioning results in a reduction in ischaemic-reperfusion injury to the heart. This beneficial effect is seen both with direct local preconditioning of the myocardium and with remote preconditioning of easily accessible distant non-vital limb tissue. Ischaemic postconditioning with a comparable sequence of brief periods of local ischaemia, when applied immediately after the ischaemic insult, confers benefits similar to preconditioning. Objective: To test the hypothesis that limb ischaemia induces remote postconditioning and hence reduces experimental myocardial infarct size in a validated swine model of acute myocardial infarction. Methods: Acute myocardial infarction was induced in 24 pigs with 90 min balloon inflations of the left anterior descending coronary artery. Remote ischaemic postconditioning was induced in 12 of the pigs by four 5 min cycles of blood pressure cuff inflation applied to the lower limb immediately after the balloon deflation. Infarct size was assessed by measuring 72 h creatinine kinase release, MRI scan and immunohistochemical analysis. Results: Area under the curve of creatinine kinase release was significantly reduced in the postconditioning group compared with the control group with a 26% reduction in the infarct size (p<0.05). This was confirmed by MRI scanning and immunohistochemical analysis that revealed a 22% (p<0.05) and a 47.52% (p<0.01) relative reduction in the infarct size, respectively. Conclusion: Remote ischaemic postconditioning is a simple technique to reduce infarct size without the hazards and logistics of multiple coronary artery balloon inflations. This type of conditioning promises clear clinical potential.